Methodologies in Critical Terrorism Studies: Gaps and Interdisciplinary Perspectives - Finden, Alice E. (Routledge Critical Terrorism Studies, 2024)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- List of illustrations -- List of contributors -- Acknowledgements -- Introduction: Methodological Plurality and Reflexivity -- SECTION I: The Field of Critical Terrorism Studies and Violence -- 1. Calibrating Violences in Critical Terrorism Studies -- 2. "Terrorism" as Abjection: Queering/Abolishing Critical Terrorism Studies -- 3. A Decolonial Mission for Critical Terrorism Studies: Interrogating the Gendered Coloniality and Colonial Function of the Dominant Discourse on Terrorism -- SECTION II: The Eurocentricity of Critical Terrorism Studies and Global South Approaches -- 4. Postcolonial Spaces and Critical Terrorism Studies: Towards a Dialogic Research Agenda -- 5. Cannibalising the Visual in Critical Terrorism Studies: A Counter-Visuality of the 01/08 Anti-democratic Attacks in Brazil -- 6. Indigenous Voice in Tackling Violent Extremism in Kenya: Coloniality and Exclusion of African Women -- SECTION III: Bridging Disciplinary and Methodological Gaps in Critical Terrorism Studies -- 7. Going Beyond the State-Centrism of Critical Terrorism Studies: Studying Counterterrorism as Contestation across Political Parties -- 8. Bringing in New Voices: Non-English Linguistic Corpora and Critical Terrorism Studies -- 9. Rethinking Methodologies in Critical Terrorism Studies: A Mixed-Method Randomised Control Trial Study on Community Reintegration of Former Boko Haram Members in Nigeria -- Index.